Team Communication DVD-based training program - fenman (Cambridge Fenman, 2007)
Understanding what needs to be communicated, and to who, is a key requirement of any effective team communication plan. The method used for transmitting messages is also important. Although technological means such as e-mail, SMS and intranet bulletin boards can be helpful, they are not always the best solution. Those in medium to large enterprises have consistently shown they prefer face to face communication via their direct supervisor to any other method.
Includes participants work book
Keywords: Team Communication